Cyclophosphamide Pulse Therapy Normalizes Vascular Abnormalities in a Mouse Model of Systemic Sclerosis Vasculopathy - Yamashita, Takashi (J Invest Dermatol, 2018)
Intravenous cyclophosphamide pulse, a standard treatment for systemic sclerosis (SSc)-related interstitial lung disease, elicits a disease-modifying effect on SSc vasculopathy, such as fostering microvascular de-remodeling. To investigate the molecular mechanism by which cyclophosphamide mitigates SSc vasculopathy, we employed endothelial cell–specific Fli1 knockout mice that mimic the functional and structural vascular abnormalities characteristic of SSc. Biweekly cyclophosphamide injection improved vascular permeability and structural abnormalities of endothelial cell–specific Fli1 knockout mice in 2 weeks and in 3 months, respectively. In endothelial cell–specific Fli1 knockout mice, a single dose of cyclophosphamide was sufficient to normalize the decreased expression of α–smooth muscle actin in dermal blood vessels and improve the impaired neovascularization in skin-embedded Matrigel plug. Under the same condition, the decreased expression of vascular endothelial cadherin, platelet-derived growth factor B, S1P(1), and CCN1 (molecules associated with angiogenesis and/or vasculogenesis) was reversed along with the reversal of endothelial Fli1 expression. In SSc patients, serum CCN1 levels were significantly increased after intravenous cyclophosphamide pulse. Taken together, these results indicate that cyclophosphamide improves Fli1 deficiency-dependent vascular changes by normalizing the expression of angiogenesis- and vasculogenesis-related molecules and endothelial Fli1, which may help to explain the beneficial effect of cyclophosphamide on SSc vasculopathy.